The Legal Position Of Marriage Through a Unified Marriage Isbat Trial At The Gorontalo Religious Court - Aneng T. Lamara (Estudiante Law Journal, 2020)
Abstract: The purpose of writing to be achieved is to know and analyze about  what is the legal status of the wife who is still bound by a legal marriage in applying for marriage confirmation through a unified marriage isbattrial? and  What are the legal implications for the legal status of the wife due to the establishment of the confirmation of marriage through a unified marriage isbat trial? This study uses a type of Normative research with two approaches, namely the legislative approach and the case approach. the results showed that:  First,  the position of the legal status of the wife who is still bound by a legal marriage in filing a marriage confirmation through a juridically integrated marriage isbat trial has violated the provisions   contained in the marriage law that expressly does not allow for the wife to marry twice before there is a divorce ruling that has permanent legal force from the Court. Second, the legal implications arising from the legal status of the wife due to the establishment of the legalization of marriage through a unified marriage isbat trial, namely the emergence of legality for legally valid wives due to not getting a divorce ruling from the Court on the previous marriage which is essentially contrary to the provisions of the marriage law on the prohibition of polyandry for the wife and opens the space for violations of the law.  from the legal side of state administration through legal smuggling at the time of issuance of marriage books. Keywords: Marriage Isbat; Ratification; Court.